Identification of maintainers and restorers using WA source CMS lines for hybrid rice breeding - Pushpam, R; Manonmani, S; Ulaganathan, V; Umadevi, M; Robin, S (ORYZA-An International Journal of Rice, 2019)
A study was undertaken for the development of new non-aromatic CMS lines and to identify the fertility restoration ability of different CMS lines of wild abortive cytoplasm for hybrid rice breeding. The materials for the present study consists of 4 CMS lines viz., TNAU CMS 2A, COMS 23A, COMS 24A, CRMS 31A and 75 male parents. Crosses were made between CMS lines and male parents and produced hybrid combinations successfully. One hundred and thirty hybrid combinations were raised in test cross nursery along with its parents and checks CORH 3, CORH 4, CO 50 and CO51. From this study, eighty testers were found to be effective restorers and eighteen as effective maintainers and thirty-two as partial restorers. The identified promising maintainers were ARB 6, JGL 17189, CB 08702, JGL 17233, JGL 17196, CB 06563, CB 06803, JGL 17190 for the CMS line TNAU CMS 2A and AU 8010, CB 248/1257, CB 204 /1557, CB 119/1261, CB 280/1235, CB 120/1858 CB 104/1801, CB 132/1819 and JGL 17233 for the CMS lines COMS 23A and COMS 24A. The tester JGL 17196 behaved as an effective maintainer for the CMS line, TNAU CMS 2A and effective restorer for the CMS line, COMS 23A. Among the 18 potential maintainers identified, back crossing was made with a recurrent parent and the progenies which are under conversion programme for the development of new non-aromatic CMS lines. Further, the effective restorers identified can be utilized in developing new hybrid combinations for commercial cultivation.